SWEAR WORDS AS A TOOL OF EVIDENCE FOR INVESTIGATION OF VERBAL CRIMES SEMANTIC AND PRAGMATIC BASED FORENSIC LINGUISTICS STUDY (UNGKAPAN MAKIAN SEBAGAI ALAT BUKTI INVESTIGASI TINDAK KEJAHATAN VERBAL KAJIAN LINGUISTIK FORENSIK BERBASIS SEMANTIK DAN PRAGMATIK) - Erwita Nurdiyanto; Gita Anggria Resticka (Jurnal Gramatika, 2021)
The linguistic forensic is one of the branches of applied linguistics related to the law i.e. language as proof in civil case or. One form of the linguistic phenomenon that is used as a tool of investigation evidence of verbal crimes is the use of the word cuss. The use of the word cuss is one of the linguistic evidence that can have a different meaning depending on the context that is behind it. The focus of this study is to identify linguistic texts containing the word that potentials affect the law. This study aims to uncover the implicit meaning of the word and describe the use of negative connotations that can lead to conflicts and legal cases. The forensic linguistic approach method is a method of implementing languages that can solve language-based problems in various legal contexts. The results of this study show that forensic linguistics on the analysis of the linguistic structure of the phrase in semantic terms, pragmatic and analysis of discourse relating to the legal texts can be utilized by the judge or the police to uncover the truth and know the violation of verbal crimes such as hate speech, humiliation, or defamation.